Trends in Weight among Undergraduate Students in a Northeast Public University - Evans, Marian; Zigmont, Victoria A. (Journal of Public Health Issues and Practices, 2020)
Objective: Increasing BMI, overweight, and obesity are urgent and grave problems in the US. The goal of this study is to begin to understand trends in overweight and obesity among undergraduate students in the U.S. to assist in informing public health education and health promotion practices. Methods: Data on self-reported weight and height were collected in 2012, 2014, and 2016 from randomly selected college students who were enrolled in a public university in Northeast US. Spearman's Rank Order Test was used to evaluate trends within specific demographic categories. Results: BMI increased for almost all studentsfrom 2012-2016. Groups with significant increases in BMI included: males, females, sophomores, and seniors. Conclusions: Results suggest the need for interventions to reduce increases in overweight and obesity that are experienced during college years. College is a critical transitional time when students adopt health behaviors that they continue into adulthood. Increasing BMI in college students indicates a need for additional research to understand the factors that contribute to the increasing trend of overweight and obesity in this population. College is an optimal setting for implementation of effective interventions that can help prevent BMI increases in this population and establish healthy behaviors for the future. Keywords: Overweight, Obesity, College Students, BMI, Spearman’s Rank, Interventions
0 citations (Crossref) [2023-10-31]
Keywords: dept.pch; peer-reviewed